1984
DOI: 10.1254/jjp.34.381
|View full text |Cite
|
Sign up to set email alerts
|

Antiulcer activity of clotiazepam in rats.

Abstract: Abstract-Effectof the anti-anxiety drug clotiazepam on the experimental gastric ulceration induced by restraint and water-immersion stress or aspirin was studied in rats. Clotiazepam prevented the development of each gastric ulcer. From the effect of clotiazepam on aspirin-induced ulceration, we presumed that clotiazepam should have some other antiulcer mechanism in addition to its action on the central nervous system.There was an appreciable correlation between the decrease in the hexosamine level of gastric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1986
1986
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…Tissue slices were stained with periodate‐Schiff/Alcian blue (AB‐PAS, pH 2.5). Observed under optical microscope (200×, Olympus CX31) and the percent area of PAS‐stained mucosal substance in the gastric mucosa was determined by an image analyzer (XTFenXi 4.0) …”
Section: Methodsmentioning
confidence: 99%
“…Tissue slices were stained with periodate‐Schiff/Alcian blue (AB‐PAS, pH 2.5). Observed under optical microscope (200×, Olympus CX31) and the percent area of PAS‐stained mucosal substance in the gastric mucosa was determined by an image analyzer (XTFenXi 4.0) …”
Section: Methodsmentioning
confidence: 99%
“…Klotiazepam ve dothiepin gibi ilaçların da farklı ülser modellerinde önemli ülseri önlemeye katkıda bulunan etkiye sahip oldukları görülmüştür. Dotiepinin ülseri önlemeye katkıda bulunan aktivitesi 5-lipooksijenaz yolağı ve yağ kökenli eikozanoidlerden birine etkisiyle oluşmuştur [11,31,32].…”
Section: ) Trisiklik Antidepresanlar (Tca)unclassified
“…Antiulcer studies with antidepressant drugs have revealed that several tricyclic antidepressant drugs, such as trimipramine [3], clotiazepam [4] and dothiepin [5], possess significant antiulcer activity against different types of ulcer models.…”
Section: Introductionmentioning
confidence: 99%